2005
DOI: 10.1002/bem.20171
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the ion cyclotron resonance effect on amino acids adsorbed at the interfaces

Abstract: In this study we show a reproduction of the Zhadin experiment, which consists of the transient increase of the electrolytic current flow across an aqueous solution of L-arginine and L-glutamic acid induced by a proper low frequency alternating magnetic field superimposed to a static magnetic field of higher strength. We have identified the mechanisms that were at the origin of the so-far poor reproducibility of the above effect: the state of polarization of the electrode turned out to be a key parameter. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…These authors showed that combined magnetic fields produce a marked effect on biological objects if they are adjusted to the ion cyclotron frequency of Ca 2þ . We have shown that the same approach to the calculation of effective frequencies is applicable to the ionic forms of some amino acids [Novikov and Zhadin, 1994], which was confirmed by later studies [Zhadin et al, 1998;Pazur, 2004;Comisso et al, 2006]. Indeed, at physiological pH values, the ionic form of the arginine molecule has an excessive positive charge (isoelectric point of arginine 11.15), which can be taken into account in the calculation by the formula of ion cyclotron resonance.…”
Section: Discussionmentioning
confidence: 62%
“…These authors showed that combined magnetic fields produce a marked effect on biological objects if they are adjusted to the ion cyclotron frequency of Ca 2þ . We have shown that the same approach to the calculation of effective frequencies is applicable to the ionic forms of some amino acids [Novikov and Zhadin, 1994], which was confirmed by later studies [Zhadin et al, 1998;Pazur, 2004;Comisso et al, 2006]. Indeed, at physiological pH values, the ionic form of the arginine molecule has an excessive positive charge (isoelectric point of arginine 11.15), which can be taken into account in the calculation by the formula of ion cyclotron resonance.…”
Section: Discussionmentioning
confidence: 62%
“…Peaks in the ionic electrolytic current of aqueous amino acid solutions placed in a static magnetic field of flux density between 10 and 80 mT, with a superimposed alternating magnetic field with frequency between 1 and 10 Hz and a flux density between 20-80 nT have been observed by some researchers (Zhadin et al, 1998;Del Giudice et al, 2002;Pazur, 2004;Comisso et al, 2006), arousing considerable interest in the biomedical studies. However, other researchers have repeated the experiment and have not observed the appearance of peaks (Adair, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…The experimental set up is similar to the one used by other researchers (Zhadin et al, 1998;Pazur, 2004;Comisso et al, 2006). Particular care has been devoted to the accuracy and control of all the experimental parameters, entering the measurements, both physical and chemical.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments such as this followed the discovery in 1985 of an unusual resonance effect caused by a simultaneous weak DC and low frequency AC magnetic field in concentrations of calcium in the nervous tissue [Liboff, 1985]. Although controversial, the unexpected Zhadin effect has been observed by a number of independent researchers [Pazur, 2004;Comisso et al, 2006;Giuliani et al, 2008], and the origin of the current has been explained as a consequence of the dynamics of the ions in the arrangement of the coherent domains of water [Del Giudice et al, 2002].…”
Section: Introductionmentioning
confidence: 96%